Effect of Managed Deficit Irrigation and Different Fertilizer Levels on Yield and some Physiological Traits of Quinoa (Chenopodium quinoa) - Hassan Fatemi Kiyan; مریم تاتاری; Mohammad Reza Tokalo; Masomeh Salehi; Kmal Haj Mohammadnia Ghalibaf (Ikufīziyuluzhī-i Giyāhān-i Zirā̒ī)
The availability of organic matter in deficit irrigation conditions can be a practical solution to compensate the negative effects of drought stress. In order to investigate the effect of deficit irrigation and chemical fertilizers on yield and some physiological traits of quinoa an experiment was conducted in 2019 as split plot based on a randomized complete block design in two locations (Mashhad and Neishabour). Irrigation levels included, I0: full irrigation, I1: irrigation at emergence stage, I2: irrigation at stem elongation stage, I3: irrigation at flowering stage, I4: irrigation at seed setting stage. Fertilizer treatments included control (no fertilizer application); chemical fertilizer application according to local practices; manure application of 10 tons; and manure application of 20 tons per hectare. Seed yield and yield components, leaf area index, crop growth rate and relative growth rate were measured. The highest 1000-seed weight was obtained in 20 tons of manure and I2 treatment in Neishabour. The lowest 1000-seed weight was obtained in 10 and 20 tons of manure and I1 in Neishabour. The lowest grain yield in I1 treatment was observed in Neishabour and the highest grain yield in I0 treatment with 20 t.ha-1 manure was observed in Mashhad. Fertilizer treatments increased crop growth rate in both experimental sites, but the effect of manure on increasing crop growth rate was greater than the effect of chemical fertilizer. However, due to the high fat content of quinoa, the use of 20 tons of manure per hectare is recommended if it is purely economic. In general, I2 treatment along with the application of manure in both places had high grain yield and dry matter production.